2015
DOI: 10.4028/www.scientific.net/msf.814.569
|View full text |Cite
|
Sign up to set email alerts
|

SiC/Cu Composite Prepared by Spontaneous Infiltration of Copper Alloy into Porous SiC Ceramic

Abstract: A porous SiC ceramic reinforced copper-matrix composite was fabricated by spontaneous infiltration of molten Cu-24at%Si alloy into the reinforcement. The influence of process parameters on the infiltration behavior and microstructure of the as-prepared SiC/Cu composite investigations showed that infiltration temperature had an important influence on the infiltration behavior, and higher infiltration temperature which decreased the viscosity of molten Cu-24Si was beneficial to the penetration. Besides, the degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…It was demonstrated that high SiC volume fraction composites can be produced by infiltrating liquid metals into packed SiC powder. This way was applied at relative low temperatures with aluminum and copper [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that high SiC volume fraction composites can be produced by infiltrating liquid metals into packed SiC powder. This way was applied at relative low temperatures with aluminum and copper [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, spontaneous infiltration is believed to be a promising route for the fabrication of SiC reinforced metal-matrix composites owing to its advantages of simple equipment, low cost and the near-to-shapes complex parts [9][10][11][12]. Silicon is commonly used as alloy element to copper and aluminum to enhance the wettability and to limit the reactivity between ceramic and liquid metal [6,[12][13][14]. On this way, one can easily consider the possibility to use melt silicon as liquid metal.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of including a high volume of ceramic filler in a metal matrix allows a greater maneuvering margin for adjusting the thermal stability and thermophysical characteristics of the composites. This way was applied at relatively low temperatures with aluminum and copper [5][6][7][8][9]. Recently, special interest has been focused on SiC ceramic-reinforced metal-matrix composites.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that high SiC volume fraction composites can be produced by infiltrating liquid metals into packed SiC powder. This way was applied successfully at relative low temperatures with aluminum and copper [15,16]. MMC can be tailored to have superior properties such as enhanced high-temperature performance, high specific strength and stiffness, increased wear resistance, better thermal and mechanical fatigue, and creep resistance than those of unreinforced alloys.…”
Section: Introductionmentioning
confidence: 99%